Measuring Debt Risk during Financial Crisis - Ramantshane, Keabetswe (Business, Management and Economics: Research Progress Vol. 8, 2024)
The global financial crisis affected many developing countries in different ways. This affected risky portfolios adversely, forcing many investors to incur losses. Financial institutions, specifically banks and small businesses, have encountered difficulty in sustaining their ability to remain stable during the financial crisis. During this period most scholars addressed the cause and risk of financial turbulence but very few studies identified the cost of debt and risk of financial turbulence. The objective of this study is to enhance the Mahalanobis model to include the measurements of cost of debt when measuring financial turbulence which essentially has an impact on the stock market. The data collected in respect of the South African Reserve Bank (SARB) and Statistics South Africa (SAS) identifies the correlation of financial turbulence in banks as well as small businesses and analyses and interprets the relationship between total liquidation of companies and total assets of banks. The crisis affected markets differently, but they all had the same results of low cash movement that resulted in a decrease in money supply that resulted in financial turmoil.